Interactive training in the russian language for students of non-language specialties - Kurmanova, B.H. (KSU publ., 2020)
The article deals with one of the ways to modernize education on a competence basis, namely, through the use of interactive forms of teaching in teaching the Russian language. Examples of interactive teaching methods in the Russian language classes are presented: brainstorming, project, debate, presentations. The use of interactive teaching methods in the classroom helps motivate students to the learning process, arouse interest in the subject and increase cognitive and intellectual ability, as well as independence in actions. The relevance of the problem is due to a sharp decrease in the cognitive and motivational interest of students in the problems of a linguistic personality. Scientific and innovation theoretical significance: identified and compared various approaches to the analysis of the motivational foundations of students; the features of the application of interactive learning technology at the university are highlighted and described; A model for the development of motivation for teaching students through interactive teaching of language disciplines at the university was developed and put into practice.
Keywords: interactive methods; brainstorming; project; business games; multimedia; technology